A Rapid One‐Pot Five Component Sequential Access to Novel Imidazo[2, 1‐b]thiazinyl‐α‐aminophosphonates. Issue 3 (8th March 2016) - Kaur, Tanpreet; Saha, Debasmita; Singh, Neetu; Singh, Udai P.; Sharma, Anuj
Abstract: A facile and rapid entry towards assembly of novel imidazo[2, 1‐ b ][1, 3]thiazinyl‐α‐aminophosphonate scaffolds through a one‐pot, sequential reaction of 2‐amino‐4 H ‐1, 3‐thiazine‐3‐one, dialdehydes, isocyanides, aromatic amines and dialkyl/aryl phosphites is demonstrated. Successive sequencing of Groebke‐Blackburn‐Bienaymé (GBB) reaction with Kabachnik Field's reaction results in the efficient formation of novel bis‐ heterocyclic frameworks. The highlights of the present protocol include survival of the aldehydic group post GBB without any protection. Additionally, simplicity of execution excluding both solvent and catalyst, cheap reagents, excellent functional group tolerance under minutes of microwave irradiation justify it to be a green protocol. Abstract : A facile and rapid entry towards assembly of novel imidazo[2, 1‐ b ][1, 3]thiazinyl‐α‐aminophosphonate scaffolds through a one‐pot, sequential reaction of 2‐amino‐4 H ‐1, 3‐thiazine‐3‐one, dialdehydes, isocyanides, aromatic amines and dialkyl/aryl phosphites is demonstrated.